Reciprocal recurrent selection in corn: tolerance to attack of the coro earworm and the fall armyworm (Lepidoptera: Noctuidae). - Fuentes, Mario (2016)
The progressive selection of yield, agronomic characteristics and quantification of damages caused by Spodoptera frugiperda (J.E. Smith) and Helicoverpa zea (Boddie), were evaluated after four selection cycles on maize populations (Zea mays L., varieties Ohio S9, Ohio S10, Mayorbela and Diente de caballo, under chemical control and natural infestation conditions. The experiments were carried out at an experimental site in a tropical agriculture research station (TARS), a USDA station located in Isabela, Puerto Rico. The experimental design consisted of random entire blocks with five repetitions, and treatments were asigned according to a factorial arrangement with parcels divided at a density of 44.444 plants/ha. Significant differences were found among populations and selection cycles for yield, plant and cob height, and percentage of insect-related losses*. The highest yield was obtained from the Ohio S 10 population with 4.824 kg/ha, and 169 kg/ha - a profit of 1.2% per selection cycle. The latest selection cycles showed a greater yield and better agronomic characteristics than the initial selection cycle of each population under improvement. Losses in yield caused by S. frugiperda and H. zea oscillated between 3-21 % and 17-28%, respectively. Ohio S9 showed the greatest los s in yield caused by these insects.